The Impact of the Introduction of a CCCTB in the EU - Danuše Nerudová; Veronika Solilová (Intereconomics, 2019)
Base erosion and profit shifting, which the majority of Member States are currently confronting, have particularly led the European Commission to reconsider the proposal and to relaunch the project known as the Common Consolidated Corporate Tax Base (CCCTB). The European Commission has published an action plan for fair and efficient corporate tax systems in the European Union in which the CCCTB is understood as a tool to fight tax evasion and tax fraud.
Keywords: 330